Potential Fraud in The Implementation of National Health Insurance in The Health Sector: Systematic Review - Rizki Nurul Fatimah; Misnaniarti Misnaniarti; Rizma Adlia Syakurah (Universitas Muhammadiyah Yogyakarta, 2021)
Fraud in the national health insurance is a form of deliberate effort to create a benefit that should not be enjoyed by individuals or institutions and could harm other parties. This study aims to further analyze the potential for fraud in the implementation of national health insurance at health facilities. The method used a systematic review based on PRISMA with a qualitative approach through descriptive analysis. The articles selection based on the specified inclusion and exclusion criteria. The study found that the potential for fraud can occur in the primary care health facilities (FKTP) and secondary care health facilities (FKRTL) in the form of potency such as inappropriate capitation fund management, maximizing the number of claims, upcoding, dissatisfaction with the salaries received, and inadequate internal controlling/supervision. As the conclusion of this study, the potential fraud in the implementation of national health insurance in Indonesia occurs in the primary care health facilities (FKTP) and secondary care health facilities (FKRTL). The prevention of potential fraud can be done by implementing the principles of Corporate Governance and the implementation of fraud prevention based on the Regulation of the Minister of Health Number 16 of 2019.